(untitled) (Scientific journal of the Fergana State University, 2024)
The climatic condition of the research object has a great influence on the selection of the type of fertilizers, the fertilizer rate, duration, method of application and efficiency. The reason is that the amount of precipitation and the thermal regime of the soil play an important role in the growth of the plant and its vegetation period. Mineral phosphorus, passing through the root system of the cotton plant, accelerates metabolic reactions, i.e. nucleotides (adenosine triphosphate, ATF), then phosphorylated glucose, nucleic acid and other reactions. It plays an important role in the exchange of energy substances attached to ATF, in the process of assimilation of mineral nutrients. the effect on the quality, but also on the agrochemical properties of the soil is important.